O envelhecimento da população mundial: um desafio novo The ageing of the world's population: a new challenge - Alexandre Kalache; Renato P. Veras; Luiz Roberto Ramos (Universidade de São Paulo, 1987)
O envelhecimento populacional é hoje um fenômeno universal, característico tanto dos países desenvolvidos como, de modo crescente, do Terceiro Mundo. São apresentados dados que ilustram a verdadeira revolução demográfica desde o início do século e estimativas até o ano 2025. Os fatores responsáveis pelo envelhecimento são discutidos, com especial referência ao declínio tanto das taxas de fecundidade como das de mortalidade. Em conjunto, tais declínios levam a um menor ingresso de jovens em populações que passam a viver períodos mais longos. Esse processo gradativo é conhecido como "transição epidemiológica" e seus vários estágios são abordados. As repercussões para a sociedade, de populações progressivamente mais idosas são consideráveis, particularmente no que diz respeito à saúde. Os padrões de mortalidade e morbidade são discutidos e o conceito de autonomia, como uma forma de quantificar qualidade de vida, é introduzido. É proposta redefinição do próprio conceito de envelhecimento, refletindo a realidade médico-social do Terceiro Mundo. São formuladas questões sobre a interação envelhecimento-mudanças sociais em curso nos países subdesenvolvidos, cujas respostas podem ser grandemente facilitadas pelo uso do método epidemiológico. Ageing has now become a universal phenomenon, of increasing importance to developed and developing countries alike. In this, the first of a series of articles on ageing in developing countries, the actual demographic revolution is discussed, with special reference to Brazil. Estimates are provided up to the year 2025. The article analyses the factors which are responsible for this ageing process - such as the rapid decline in fertility and mortality rates that many Third Word countries have been experiencing over the last few years - and the various gradual stages of this process, which is usually referred to as the 'epidemiological transition', are discussed. The consequences for any society with a population that is gradually becoming older are considerable, and are of particular importance for the Health Sector. The article discusses the changing morbidity and mortality patterns and the concept of autonomy as a possible way to quantify quality of life is introduced. On this particular point a suggestion is made to redefine the concept of 'Ageing', in order to take into consideration the context in which senior adults in the Third World live. Finally, the article addresses itself to points relating to the interaction of ageing and social change. That there is such an interaction is apparent in developing countries and this raises questions to which answers could be found through the use of the epidemiological method.